The Stress Management Methods to Improve Student Well-Being(A Systematic Literature Review) - Fatih, Amri; Ramli, Muhammad; Wahyuni, Fitri (International Journal of Research in Counseling, 2025)
Improving student well-being is crucial to be researched and developed as it relates to the enhancement of students' social, emotional, and academic competencies and serves as a defense mechanism against emotional disorders experienced by students, such as depression, suicide, self-harm, antisocial behavior (bullying and violence), and substance abuse. One method to enhance student well-being is stress management, as one of the factors affecting student well-being is the level of academic stress. The aim of this study is to identify stress management methods previously employed by researchers to improve student well-being. This research utilized a systematic literature review method. The results revealed that out of 239 articles identified in the initial stage, 19 relevant articles met the criteria set by the researchers. The stress management methods identified include relaxation and meditation methods, mindfulness methods, cognitive therapy, and behavior modification methods.